The Persian Gulf and South Asia : prospects and problems of inter-regional cooperation - Sen Gupta, Bhabani, 1921-; Centre for Policy Research (New Delhi, India) (New Delhi : South Asian Publishers, 1987)
Papers presented at a seminar organized by the Centre for Policy Research, March 1986.
Companion volume to: Regional cooperation and development in South Asia.
Includes bibliographies and index.
Rashid
Keywords: Persian Gulf Region -- Politics and government; Persian Gulf Region -- Relations -- South Asia; South Asia -- Relations -- Persian Gulf Region; Persian Gulf Region -- Economic conditions